The Legal Authority of Administrative Investigations and Their Influence on Criminal Proceedings - Ali Hussein Al-izzy, Assist. Lect . Hazim (Basra studies journal, 2025)
The success of a state's administrative system and its public services hinges on several fundamental pillars, foremost among them the extent to which public employees fulfill their duties, uphold ethical standards, and demonstrate integrity and honesty—within the framework of laws and regulations governing public service. Accordingly, public administration in state institutions—regardless of their nature—strives to ensure that its operations conform to the constitution and the law. This is particularly important, as the administration is responsible for enforcing the law and maintaining the smooth operation of public services, which provide essential benefits to both individuals and society at large. Iraq is considered the first Arab country to enact legislation regulating public employee discipline. This legislation clearly defines the duties of public employees and the penalties applicable in cases of violation. Since a public employee’s failure to meet their legal obligations disrupts the continuity and efficiency of public services—an objective at the core of administrative law—the law holds such employees accountable. When an administrative violation occurs, the employee is subject to internal investigative procedures, and if the violation is substantiated, the competent authority imposes the appropriate disciplinary sanction. In some instances, the act may also constitute a criminal offense under the Penal Code. Consequently, the legislator has established specific penalties for public employees who breach their duties and responsibilities.